Eric - Tan, Shaun (Scholastic Press, 2020)
"When a foreign exchange student comes to live with a typical suburban family, he brings with him a boundless sense of curiosity--and a stream of unexpected questions (which his hosts are never quite sure how to answer). But when the moment comes to say good-bye, a beautiful surprise awaits, and a gift the family will never forget."--Publisher's website.